Cue-induced craving and physiological reactions in recently and long-abstinent heroin-dependent patients - Zhao, Min (2011)
OBJECTIVE: To understand the different patterns of cue-induced craving and physiological reactions among recently abstinent and long- abstinent heroin-dependent patients. METHOD: 26 healthy adult controls (HC), 29 long-abstinent (more than 1 year, LA), and 26 recently abstinent (less than 1 month, RA) heroin-dependent individuals were exposed to heroin-related and neutral video cues, one video per session, on different days in random order. Self-reported heroin craving by a 10-point visual analog scale (VAS), physiological reactions [Skin conductance (SC), muscle electromyography (MEG), skin temperature (TEMP)] and cardiovascular arousal [heart rates (HR), systolic blood pressure (HBP) and diastolic blood pressure (LBP)] were assessed at baseline and after exposure. RESULTS: Both heroin-abstinent groups showed increased heroin craving, SC, MEG, HR, SBP and LBP after exposure to heroin-related video, compared to the control group and compared to exposure to the neutral video. Except the RA group showed more HR changes, changes of heroin craving, SC, MEG, HR, SBP and LBP after exposure to the heroin cue video were not different between the LA and RA groups. CONCLUSIONS: Abstinent heroin-dependent patients had elevated craving and physiological reactions after exposure to videos containing heroin-related cues and the cue induced responses still occurred in long-abstinent patients. This phenomenon should be addressed in treatment and recovery services for heroin dependence.